Ending child labour in domestic work and protecting young workers from abusive working conditions - Blagbrough, Jonathan; International Labour Office. International Pogramme on the Elimination of Child Labour. Governance and Tripartism Depatment (Geneva International Labour Organization (ILO), 2013)
Within the framework of the two ILO fundamental conventions on child labour and the recently adopted instruments on decent work for domestic workers, this new report sets the scene for a better understanding of child labour in domestic work. It outlines why involvement of children in domestic work should be a global concern and presents the basic concepts in this area as well as the required responses. It looks into child domestic work as a social development priority, a human rights concern and a gender equality challenge.  It provides detailed information on current data regarding the estimated number of child domestic workers worldwide. It also explores the ambiguity of the working relationship, the discrimination and isolation associated with the practice, the hazards and risks of this type of work, as well as the vulnerability to violence and to abuse to which child domestic workers are too often exposed. It also explores policy responses to child labour and underlines the key role of the social partners and civil society organizations in the fight against child labour in domestic work. The report concludes by making a call for specific action towards ending child labour and protecting young workers in domestic work.
Executive summary -- 1. Understanding child domestic work -- 2. Why focus on child domestic work? -- 3. Global estimates on child domestic work -- 4. A complex phenomenon: Key features of child domestic work -- 5. Policy responses to child domestic work -- 6. The role of social partners -- 7. Reaching and supporting child domestic workers: Civil society responses -- Recommendations -- References
Includes bibliographical references(P.83-87)
Keywords: Labour force; LABOUR MARKET; CHILD LABOUR; DOMESTIC WORKERS; LABOUR POLICY; CIVIL SOCIETY; ILO Declarations